Genus Salvia: Its Secondary Metabolites and Roles in the Treatment of Common Cancer Types in Men and Women - Martinez-Salinas, J; Morales-Munoz, B; Jaimes-Fernandez, L (CRC Press, 2023)
The genus Salvia, belonging to Lamiaceae, is represented by approximately one thousand species worldwide. It is known that these species have many of the secondary metabolites such as terpenes, phenolics, and so on. The Salvia species traditionally and scientifically have been used in cancer treatment for many years due to these secondary metabolites. Cancer is the second leading cause of death after heart disease worldwide. Lung, breast, liver, stomach, colon, prostate, and cervical among the cancer species are the most common types in men and women. In addition, many alternative natural resources are used to reduce the mortality rate due to cancer, one of which is genus Salvia. This chapter describes pharmacological and molecular roles and secondary metabolites of some important species of the genus Salvia in the treatment of the common cancer types. © 2023 José L. Martinez, Alfred Maroyi and Marcelo L. Wagner.